Credibility of YouTube™ videos on root canal treatment in children - Nezy Susan Varghese; Joe Mathew Cherian; Abi M Thomas (Wolters Kluwer Medknow Publications, 2022)
Background: A lot of videos on root canal treatment in children are available on YouTube™ but no quality checks are present. Addressing this is critical so that parents and dentists know why root canal in children is important including the explanation of procedural steps regarding treatment undertaken. Aim: The aim of this study is to analyze and grade YouTube™ videos on root canal treatment in children and assess whether it provides beneficial information for patients and dentists. Materials and Methods: Variables such as number of views, duration (minute), days since upload, number of comments, number of likes, number of dislikes, interaction index, and viewing rate were tabulated for selected 57 videos. Statistical Analysis: Selected videos were statistically analyzed using a 15-point scoring system and evaluated using SPSS software. Finally, the obtained data sets were classified as low-, moderate-, and high-content videos. Fisher's exact test was used to compare between proportions. Results: Based on the tabulated variables, most of the videos were low (n = 31) and moderate content (n = 24), which dentists mostly uploaded. There was no statistical significance between the video types and content score groups (P > 0.05). The most frequently mentioned issues were procedure (84.21%), obturating materials (75.44%), and etiology (63.16%). The least mentioned subjects were indications (24.56%) and importance (22.81%). Conclusion: From this study, YouTube™ videos on root canal treatment in children were of low and moderate quality. Hence, high-quality videos are essential for providing awareness among patients and dentists.